A condition-based opportunistic maintenance strategy for multi-component system. (January 2019) - Zhao, Hongshan; Xu, Fanhao; Liang, Botong; Zhang, Jianping; Song, Peng
As a new dynamic maintenance strategy, the condition-based opportunistic maintenance strategy for multi-component system is presented in this work. In the strategy, the degeneration of each component is described by Weibull proportional hazards model or Weibull proportional intensity model, and the condition indicator is defined to characterize the operating state of each component. Then, when and how to maintain a component can be confirmed by comparing the value of the condition indicator with that of the maintenance threshold function. Condition-based maintenance will be implemented on a component if the value of its condition indicator exceeds that of its condition-based maintenance threshold function. Meanwhile, opportunistic maintenance will also be implemented on a component if the value of its condition indicator exceeds that of its opportunistic maintenance threshold function. The two maintenance threshold functions can be determined by minimizing maintenance cost. Finally, taking the wind turbine as an example of a multi-component system, simulation analyses are described to validate the feasibility and effectiveness of the condition-based opportunistic maintenance strategy.